2015
DOI: 10.1038/ismej.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomes reveal functional variation in diatom communities from the Antarctic Peninsula

Abstract: Functional genomics of diatom-dominated communities from the Antarctic Peninsula was studied using comparative metatranscriptomics. Samples obtained from diatom-rich communities in the Bransfield Strait, the western Weddell Sea and sea ice in the Bellingshausen Sea/Wilkins Ice Shelf yielded more than 500K pyrosequencing reads that were combined to produce a global metatranscriptome assembly. Multi-gene phylogenies recovered three distinct communities, and diatom-assigned contigs further indicated little read-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 88 publications
3
33
0
Order By: Relevance
“…(2015),Allen et al (2011), Bender et al (2014,Bertrand et al (2012),Gutowska et al (2017),Hockin et al (2012),Lommer et al (2012),McRose et al (2014),Paerl et al (2016),Pearson et al (2015),Pourcel et al (2013),Smith et al, (2016) andWolfe-Simon et al (2006). [Cytosol] ISIP1: iron starvation-induced protein 1; ISIP2A: iron starvation-induced protein 2A; ISIP3: iron starvation-induced protein 3; ABC.FEV.S: iron complex transport system substrate-binding protein; ABC.FEV.A: Iron (III) dicitrate transport ATP-binding protein; ACACA: biotin carboxylase; HSP70: heat shock protein 70 kDa 1/8; TYR: tyrosinase; NRT2: nitrate transporter; AMT: ammonium transporter; NR: nitrate reductase; NIRB: NADPH-nitrite reductase; UTP: urea transporter; SLC14: solute carrier family 14 (urea transporter); URE: urease; ARG: arginase; ASL: argininosuccinate lysase; ASSY: argininosuccinate synthase; AQP: aquaporin; THIC: phosphomethylpyrimidine synthase; THIDE: hydroxymethylpyrimidine kinase; THIG: thiazole synthase; TPK: thiamine pyrophosphokinase; COBH: precorrin-8X/cobalt-precorrin-8 methylmutase; COBB: cobyrinic acid a,c-diamide synthase; COBN, COBS, COBT: cobaltochelatase; COBR: cob(II)yrinic acid a,c-diamide reductase; COBA: cob(I)alamin adenosyltransferase; COBQ: adenosylcobyric acid synthase; COBD: adenosylcobinamide-phosphate synthase; COBP: adenosylcobinamide kinase; COBU: nicotinate-nucleotide-dimethylbenzimidazole phosphoribosyltransferase; COBC: alpha-ribazole phosphatase; COBS: adenosylcobinamide-GDP ribazoletransferase; CBA1: cobalamin acquisition protein 1.…”
mentioning
confidence: 99%
“…(2015),Allen et al (2011), Bender et al (2014,Bertrand et al (2012),Gutowska et al (2017),Hockin et al (2012),Lommer et al (2012),McRose et al (2014),Paerl et al (2016),Pearson et al (2015),Pourcel et al (2013),Smith et al, (2016) andWolfe-Simon et al (2006). [Cytosol] ISIP1: iron starvation-induced protein 1; ISIP2A: iron starvation-induced protein 2A; ISIP3: iron starvation-induced protein 3; ABC.FEV.S: iron complex transport system substrate-binding protein; ABC.FEV.A: Iron (III) dicitrate transport ATP-binding protein; ACACA: biotin carboxylase; HSP70: heat shock protein 70 kDa 1/8; TYR: tyrosinase; NRT2: nitrate transporter; AMT: ammonium transporter; NR: nitrate reductase; NIRB: NADPH-nitrite reductase; UTP: urea transporter; SLC14: solute carrier family 14 (urea transporter); URE: urease; ARG: arginase; ASL: argininosuccinate lysase; ASSY: argininosuccinate synthase; AQP: aquaporin; THIC: phosphomethylpyrimidine synthase; THIDE: hydroxymethylpyrimidine kinase; THIG: thiazole synthase; TPK: thiamine pyrophosphokinase; COBH: precorrin-8X/cobalt-precorrin-8 methylmutase; COBB: cobyrinic acid a,c-diamide synthase; COBN, COBS, COBT: cobaltochelatase; COBR: cob(II)yrinic acid a,c-diamide reductase; COBA: cob(I)alamin adenosyltransferase; COBQ: adenosylcobyric acid synthase; COBD: adenosylcobinamide-phosphate synthase; COBP: adenosylcobinamide kinase; COBU: nicotinate-nucleotide-dimethylbenzimidazole phosphoribosyltransferase; COBC: alpha-ribazole phosphatase; COBS: adenosylcobinamide-GDP ribazoletransferase; CBA1: cobalamin acquisition protein 1.…”
mentioning
confidence: 99%
“…Molecular-level tools that can track transcripts, proteins, or even metabolites and biochemicals in a taxon-specific way are increasingly being used in cultures and field populations to track metabolic capacity and physiological responses (16)(17)(18)(19)(20)(21)(22)(23). Molecular assessment of physiology for eukaryotic populations is most tractable in coastal systems with high biomass (17,18); thus, in oligotrophic ocean regions, molecular studies of physiology have typically been limited to the numerically abundant members of the microbial community: picoplankton (cyanobacteria, heterotrophic bacteria, and small picoeukaryotes).…”
Section: Significancementioning
confidence: 99%
“…The lack of relevant taxa in the databases also hampers the use of mRNA for lower level taxonomic assignments (Supporting Information S2). The relative scarcity of diatom rhodopsins compared to other studies (Marchetti et al ., ; Pearson et al ., ) could be due to the dominance of Thalassiosira spp at BAB (Supporting Information Fig. S1).…”
Section: Discussionmentioning
confidence: 97%
“…High proton‐pumping rhodopsin mRNA expression at BAB agrees with a study of O. marina where rhodopsin was the most highly expressed nuclear‐encoded gene in the EST library (Slamovits et al ., ). Xanthorhodopsin transcripts were also reported as abundant in marine eukaryotic metatranscriptomes from the North Pacific (Marchetti et al ., ) and Antarctica (Pearson et al ., ). Interestingly, our reanalysis of existing data revealed that eukaryotic proteorhodopsins were also numerous in several published eukaryotic metatranscriptome studies (Fig.…”
Section: Discussionmentioning
confidence: 97%